Querying structured information sources on the Web. (7th July 2010) - Mergen, Sergio; Freire, Juliana; Heuser, Carlos A.
To provide access to heterogeneous data distributed over the Web, we propose a solution that merges the expressiveness of information integration systems with the flexibility found in dataspace-aware search engines. Our approach requires neither a mediated schema nor source mappings. In the absence of a mediated schema, the user formulates structured queries based on what she expects to find. We demonstrate the feasibility of this approach by providing a query interface for integrating hundreds of (real) structured Web information sources. We also discuss experimental results which indicate that our query rewriting algorithm is both effective and scalable.